Around the World in 80 Days - Jules Verne (Blackmask Online, 2009)
One ill-fated evening at the Reform Club, Phileas Fogg rashly bets his companions that he can travel around the entire globe in just eighty days -- and he is determined not to lose. Breaking the well-established routine of his daily life, the reserved Englishman immediately sets off for Dover, accompaned by his hot-blooded manservant Passepartout. Traveling by train, steamship, sailboat, sledge, and even elephant, they must overcome storms, kidnappings, natural disasters, Sioux attacks, and the dogged Inspector Fix of Scotland Yard -- who believes that Fogg has robbed the Bank of England -- to win the extraordinary wager. Around the World in 80 Days gripped audiences on its publication and remains hugely popular, combining exploration, adventure, and a thrilling race against time.